REDUCING SYMPTOMS OF MENTAL EMOTIONAL DISORDERS IN ADOLESCENTS THROUGH SELF-HELP GROUP THERAPY - Sari, Amelia Wulan; Arfianto, Muhammad Ari; Pramudianingtias, Ajeng; Purbaningrum, Setia; Salsa, Sefira Khoirotus; Rahayu, Nanda Putri (Poltekkes Kemenkes Jakarta III, 2025)
Adolescence is a transitional stage marked by biological, emotional, and cognitive changes that increase the risk of developing mental-emotional disorders such as anxiety, depression, and emotional instability. WHO report that 10–20% of adolescents face mental health problems, influenced by factors such as family conflict, peer pressure, and excessive social media use. Without early intervention, these disorders may lead to long-term consequences including chronic psychiatric conditions and increased suicide risk. This study aims to analyze the effect of SHG therapy in reducing emotional and mental disorders in adolescents. A quantitative, pre-experimental one-group pretest-posttest design was used. The sample consisted of 76 junior high school students in grades VII and VIII in Malang Regency, selected through total sampling. SHG therapy was conducted based on the Specialist Mental Health Nursing Standard Operating Procedure in four structured stages: problem identification, planning, problem solving, and evaluation. The intervention was delivered across 17 meetings divided into four sessions, facilitated by a trained mental health nurse and five facilitators. Mental-emotional disorders were assessed using the validated Pediatric Symptom Checklist-17 (PSC-17). Participants had PSC scores ≥15 and consented to full participation. Data were analyzed using the Wilcoxon test. The mean score for emotional and mental disorders decreased from 17.16 (SD = 5.001) before the intervention to 15.63 (SD = 6.092) after (p = 0.001), reflecting a 9% reduction. SHG therapy significantly reduces emotional and mental disorders in adolescents and holds potential for implementation in school-based mental health initiatives